Pirata Est Hostis Generis Humani The Malaysian Context - Norfadhilah Mohd Ali; Hendun Abd. Rahman Shah (Universiti Sains Islam Malaysia, 2024)
So much as the world has seen piracy as an un justified illegal act, Malaysia also shares the same concern. A study of the term piracy in the Malaysian context inevitably opens a legal discussion altogether: This article will discuss on the Malaysian legal position of piratical acts with some comparisons with the International Law.